Damage mechanics and micromechanics of localized fracture phenomena in inelastic solids - Voyiadjis, G. Z.; International Centre for Mechanical Sciences; SpringerLink (Online service). (Wien New York Springer, 2011)
This book resulted from a series of lecture notes presented in CISM, Udine in July 7 -11, 2008. The papers inform about recent advances in continuum damage mechanics for both metals and metal matrix composites as well as the micromechanics of localization in inelastic solids. Also many of the different constitutive damage models that have recently appeared in the literature and the different approaches to this topic are presented, making them easily accessible to researchers and graduate students in civil engineering, mechanical engineering, engineering mechanics, aerospace engineering, and material science.
Part I: Consistent Non Local Coupled Damage -- Model and Its Application in Impact Response -- of Composite Materials -- 1 Prologue -- 2 Nonlocal formulation of the highvelocity impact -- induced damage -- 3 Mechanics of small damage in fiber reinforced -- composite materials -- composite materials -- 4 A Comparative Study of Damage Variables in -- Continuum Damage Mechanics -- Continuum Damage Mechanics -- 5 Computational aspects of the proposed theory -- 6 Verification and validation of the theoretical formulation -- 7 Application of the theory in studying high velocity -- contact problems -- 8 Conclusions -- Part II: Advances in Statistical Damage Mechanics -- (SDM): New Modeling Strategies -- 1 Introduction: from Continuum to Discrete Modeling -- 2 One Dimensional Models: Parallel Bundles Systems -- (PBS) -- 3 Higher Dimensional Models: Spring Networks -- 4 More Related Work -- 5 Concluding Remarks -- Appendix 1: Notes About Numerical Solution Schemes -- Appendix 2: The One-way Correlation Hypothesis References -- Part III: Application of the Thermodynamical -- Theory of ElastoViscoplasticity in Modern Manufacturing -- Processes -- 1 Prologue -- 2 The Thermodynamical Theory of Elasto-Viscoplasticity -- 3 Constitutive Modelling for Dynamic Cyclic Loadings -- 4 Localization and Localized Fracture Phenomena -- relations -- 5 Numerical Analysis of Macrocrack Propagation -- along a Bimaterial Interface under Dynamic Loading -- Processes -- 6 Numerical Investigation of Dynamic Shear Bands -- in Inelastic Solids as a Problem of Mesomechanics -- 7 Numerical Investigation of Localized Fracture -- Phenomena in Inelastic Solids -- 8 Epilogue -- References -- Part IV: Safety of Concrete and Masonry Structures -- under Unusual Loadings -- 1 Some remarks on damage and localized fracture -- 2 Introduction -- 3 Cumulative Fracture Criterion for brittle materials -- 4 Numerical simulation -- 5 Engineering structure subjected to explosion -- 6 Conclusions -- Bibliography -- Part II: Advances in Statistical Damage Mechanics -- (SDM): New Modeling Strategies -- 1 Introduction: from Continuum to Discrete Modeling -- 2 One Dimensional Models: Parallel Bundles Systems -- (PBS) -- (SDM): New Modeling Strategies -- 1 Introduction: from Continuum to Discrete Modeling -- 2 One Dimensional Models: Parallel Bundles Systems -- (PBS) -- 3 Higher Dimensional Models: Spring Networks -- 4 More Related Work -- 5 Concluding Remarks -- Appendix 1: Notes About Numerical Solution Schemes -- Appendix 2: The One-way Correlation Hypothesis References -- Appendix 1: Notes About Numerical Solution Schemes -- Appendix 2: The One-way Correlation Hypothesis References -- Part III: Application of the Thermodynamical -- Theory of ElastoViscoplasticity in Modern Manufacturing -- Processes -- 1 Prologue -- 2 The Thermodynamical Theory of Elasto-Viscoplasticity -- Part III: Application of the Thermodynamical -- Theory of ElastoViscoplasticity in Modern Manufacturing -- Processes -- 1 Prologue -- 2 The Thermodynamical Theory of Elasto-Viscoplasticity -- 3 Constitutive Modelling for Dynamic Cyclic Loadings -- 4 Localization and Localized Fracture Phenomena -- relations -- 5 Numerical Analysis of Macrocrack Propagation -- along a Bimaterial Interface under Dynamic Loading -- Processes -- 6 Numerical Investigation of Dynamic Shear Bands -- in Inelastic Solids as a Problem of Mesomechanics -- 7 Numerical Investigation of Localized Fracture -- Phenomena in Inelastic Solids -- 8 Epilogue -- References -- Part IV: Safety of Concrete and Masonry Structures -- under Unusual Loadings -- 1 Some remarks on damage and localized fracture -- 2 Introduction -- 3 Cumulative Fracture Criterion for brittle materials -- 4 Numerical simulation -- 5 Engineering structure subjected to explosion -- 6 Conclusions -- Bibliography -- Bibliography.
Electronic reproduction.
Keywords: Continuum damage mechanics; Micromechanics; Composite materials; Solids -- Mechanical properties; Plasticity; Electronic books